THE MYTH OF REINCARNATION IN NOVEL HEAVEN OFFICIAL’S BLESSING BY MO XIANG TONG XIU - Linda Huda Winata; Atinia Hidayah (CLLiENT (Culture, Literature, Linguistics, and English Teaching), 2022)
This research is conducted to analyze the Myth of Reincarnation in Novel Heaven Official's Blessing by Mo Xiang Tong Xiu through the term Three Realm. The researcher used the qualitative method to examine the problem. The theory and approaches that the researcher used is the Cultural Studies, Myth of Reincarnation, Novel, and Fiction. The result of this study show that the myth of reincarnation can be seen through the term three realm. The term three realm included mortal realm, heavenly realm, and ghost realm.